2003
DOI: 10.1046/j.1570-7458.2003.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for resistance in apple cultivars to lightbrown apple moth, Epiphyas postvittana, and greenheaded leafroller, Planotortrix octo, and its relationship to field damage

Abstract: The mature leaves of 38 apple (Malus domestica Borkh.) (Rosaceae) cultivars were screened for resistance to laboratory colonies of Epiphyas postvittana (Walker) and Planotortrix octo Dugdale (Lepidoptera: Tortricidae) by measuring larval survival and development rate, and pupal weight, in no‐choice laboratory bioassays in early summer. There were few cultivar effects on larval mortality but Nevis 1, A40R04T119, and ‘Sir Prize’ reduced survival of E. postvittana. Effects on development time and weight were corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…The use of resistant cultivars that are less susceptible to herbivores (direct resistance) or that are supporting biocontrol agents (indirect resistance) is a promising alternative approach for pest control (Wearing et al. ; Hogmire and Miller ; Smith and Clement ). Concerning common diseases such as scab (caused by Venturia inaequalis ), fire blight ( Erwinia amylovora ) or mildew ( Podosphaera leucotricha ), cultivars expressing resistance have already been employed successfully, substantially reducing fungicide applications (Fischer and Fischer ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of resistant cultivars that are less susceptible to herbivores (direct resistance) or that are supporting biocontrol agents (indirect resistance) is a promising alternative approach for pest control (Wearing et al. ; Hogmire and Miller ; Smith and Clement ). Concerning common diseases such as scab (caused by Venturia inaequalis ), fire blight ( Erwinia amylovora ) or mildew ( Podosphaera leucotricha ), cultivars expressing resistance have already been employed successfully, substantially reducing fungicide applications (Fischer and Fischer ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering resistance to herbivores, however, hardly any appropriate cultivars are commercially available (Hogmire and Miller 2005;Stoeckli et al 2011), although several studies have addressed resistance of different apple cultivars to arthropod herbivores including the apple blossom weevil Anthonomus pomorum (Curculionidae) (Kalinov a et al 2000;Mody et al 2015), several aphid species (Aphididae) (Miñarro and Dapena 2007;Stoeckli et al 2008a) and the codling moth Cydia pomonella (Tortricidae) (Goonewardene et al 1975(Goonewardene et al , 1979Hogmire and Miller 2005;Stoeckli et al 2008bStoeckli et al , 2009a). Furthermore, genes and quantitative trait loci (QTLs) for pest resistance in apple were identified for future markerassisted breeding of resistant cultivars (Roche et al 1997;Wearing et al 2003;Bus et al 2008;Stoeckli et al 2008cStoeckli et al , 2009a.…”
Section: Introductionmentioning
confidence: 99%
“…Once the nymphs passed the third instar on this accession, they grew into adults in both experiments. Wearing et al (2003) suggested that slow development, reduced growth and higher mortality of leafroller larvae (Lepidoptera, Tortricidae) on apple cultivars were caused by antibiosis. Moreover, low settlement rate of first instar larvae and low fecundity of adult leafroller moths were caused by the antixenosis properties of the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Wearing et al [61] developed a ranking system based on development time and pupal weight for three species of leafrollers feeding on different apple genotypes.…”
Section: Resistance Indicesmentioning
confidence: 99%